Solvability Conditions for Some Systems of Nonlinear Non-Fredholm Elliptic Equations - Vougalter, Vitali (Discontinuity, Nonlinearity, and Complexity, 2026)
We establish the existence and uniqueness of standing solitary wavelike solutions in H2 for certain systems of nonlocal nonlinear equations. These problems involve second order differential operatorswithout Fredholm property.